PERGESERAN KONFLIK SOSIAL KEAGAMAAN DI INDONESIA - Sudirman Tebba (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
One feature that marks religious social conflicts in the past with different social conflicts going on right now, that social conflict in the past are vertical, because the movement aimed against the Dutch colonial government, were social conflicts now occur among citizens who have different political and economic interest, which they happen to different religions. Thus, it may be said that the socio-religious conflict has now shifted compared to social movements in the past. That’s because our interests are first against the Dutch colonialists considered infidels, was now his interests are economic opportunities and political struggles, it’s just covered with religious issues in order to gain broad support among the group. This paper would like to elaborate a shift in socio-religious conflict in Indonesia. KEY WORDS:Religious Social Conflict, New Order, Political Interest, Economic Interest, Dutch Colonial Government, Moslem, Christian.